Effects of Second Language Acquisition on Executive Functioning in Older Adults in France - Martin, Camille (International Journal of Linguistics, 2024)
Purpose: The aim of the study was to analyze the effects of second language acquisition on executive functioning in older adults in France. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Research on second language acquisition in older adults in France indicates that learning a new language can boost cognitive abilities like problem-solving and multitasking. It enhances memory retention and cognitive flexibility, vital for maintaining mental acuity. Language learning stimulates brain regions linked to executive functions, potentially reducing cognitive decline and offering protective benefits against neurodegenerative diseases in aging populations. These findings highlight the cognitive advantages of bilingualism among older adults in France. Unique Contribution to Theory, Practice and Policy: Bilingual advantage hypothesis, cognitive reserve theory & neuroplasticity theory may be used to anchor future studies on the effects of second language acquisition on executive functioning in older adults in France. Encourage lifelong learning programs that include SLA courses for older adults in France. Advocate for the inclusion of SLA programs in public health initiatives aimed at promoting cognitive health among older adults. Policy frameworks should support funding and infrastructure for community-based language learning initiatives.